The Effect of Applying the Eligibility Principle in Credit Distribution to Business Actors on MSME Performance: Case Study of MSME Actors in Malang City, Indonesia - Barli Novirin (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2025)
The study titled The Impact of Applying the 5C Principle in Credit Allocation to Entrepreneurs on Business Performance (Case Study of Entrepreneurs in Malang City). This study aims to analyze and identify the application of the 5C principle (Character, Capacity, Capital, Guarantee, and Conditions) in credit distribution to debtors and its impact on business performance in Malang City. This research is a quantitative analysis of the characteristics of loan distribution (5C) to entrepreneurs and their company performance. Observation, interviews gathered data, and the distribution of questionnaires to 30 respondents utilizing purposeful random sampling methods. The analysis employed linear regression and hypothesis testing. This study's findings demonstrate that credit distribution (5C) to entrepreneurs positively influences business success in Malang City. The analysis and results obtained in this study indicate several significant findings warrant attention. Specifically, credit distribution may serve as a foundation for enhancing business performance in Malang City. Recommendations for business operators in Malang City include implementing a transparent evaluation process, providing training and education, and fostering long-term relationships with Micro, Small, and Medium Enterprises (MSMEs).